Sistem Pakar Metode Forward Chaining Untuk Psikoterapi Kejiwaan Terhadap Penyakit Kepribadian Genetik - Wahyudi Wahid; Gunadi Widi Nurcahyo; Sumijan Sumijan (SEULANGA SYSTEM PUBLISHER, 2020)
The problem with personality disease is that the disorder experienced cannot be easily identified because it tends to be ignored. Most people who experience symptoms of the disorder are still reluctant to see a doctor or a psychiatrist. This is due to several limitations such as limited places for consultation or psychiatrists. With these limitations the role of the Expert System is very important in solving a problem, the problem is a personality disease. The purpose of building this Expert System is to help people who suffer from personality problems consult online without having to come directly to a psychiatrist. This expert system will later become a solution to these genetic personality problems. So that people are no longer difficult to see a doctor or psychiatrist. All data to be used are sourced from experts. Forward Chaining is used in this research as a method. The search technique that begins with the facts obtained, then adjusts the rule model that has been built is called Forward Chaining. Observations will result in a website-based Expert System product that users can access online. The accuracy of the system has been tested by related parties and results in a faster and more efficient information. The conclusion of this research is to help people to diagnose the symptoms of personality disorder that they experience unconsciously and the test results can clearly detect genetic personality disease.